2019
DOI: 10.1634/theoncologist.2019-0103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 21-Gene Breast Cancer Assay on Treatment Decision for Patients with T1–T3, N0–N1, Estrogen Receptor-Positive/Human Epidermal Growth Receptor 2-Negative Breast Cancer: Final Results of the Prospective Multicenter ROXANE Study

Abstract: Background The ROXANE Italian prospective study evaluated the impact of the 21‐gene Recurrence Score (RS) results on adjuvant treatment decision for patients with early breast cancer. Materials and Methods Nine centers participated. Physicians used the RS test whenever unsure about adjuvant treatment recommendation for patients with estrogen receptor‐positive/human epidermal growth receptor 2‐negative, T1–T3, N0–N1 early breast cancer. Pre‐RS and post‐RS treatment recommendations were collected. Results A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
5
13
0
Order By: Relevance
“…A pooled analysis of four prospective European studies assessing the impact of using the OncotypeDX © recurrence score in node-negative HR+/HER2− early breast cancer demonstrated that chemotherapy recommendation rate decreased from 55% to 34% [ 111 , 112 ]. Similar results were reported in node-negative [ 113 ] but also node-positive early breast cancer [ 114 , 115 , 116 ]. The Prosigna © PAM50 [ 117 , 118 , 119 , 120 ] and EndoPredict © [ 121 ] assays also demonstrated a 20–35% decreasing of chemotherapy indications in HR+/HER2− early breast cancer.…”
Section: How Do Gene Expression Signatures Influence Clinical Decisions?supporting
confidence: 88%
“…A pooled analysis of four prospective European studies assessing the impact of using the OncotypeDX © recurrence score in node-negative HR+/HER2− early breast cancer demonstrated that chemotherapy recommendation rate decreased from 55% to 34% [ 111 , 112 ]. Similar results were reported in node-negative [ 113 ] but also node-positive early breast cancer [ 114 , 115 , 116 ]. The Prosigna © PAM50 [ 117 , 118 , 119 , 120 ] and EndoPredict © [ 121 ] assays also demonstrated a 20–35% decreasing of chemotherapy indications in HR+/HER2− early breast cancer.…”
Section: How Do Gene Expression Signatures Influence Clinical Decisions?supporting
confidence: 88%
“…The results showed that in 50% of the patients for whom chemotherapy was initially recommended according to traditional clinical practice, the Oncotype DX RS was low, thus allowing delivery of hormone therapy only; on the other hand, in only 4% of the patients for whom hormone therapy alone was originally recommended (about two-thirds of the patients in the study), the Oncotype DX test RS was high, providing evidence of a clinical benefit from adding chemotherapy. The results of the BONDX study, 15 in line with the literature and in particular with a previous Italian study (ROXANE study), 16 confirm that the multigene tests bear clinical utility, improve quality of life, and are cost-effective for the healthcare system.…”
supporting
confidence: 84%
“…Patients with RS results <11 were treated with hormone therapy only, while patients with high RS results (RS >25) received chemotherapy associated with hormone therapy. Patients with intermediate RS results (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were randomized to hormone therapy only or chemotherapy associated with hormone therapy. The results demonstrated (with a level of evidence 1A) that patients with RS results 11-25 do not benefit from the addition of chemotherapy to hormone therapy and can be safely spared its toxicities.…”
mentioning
confidence: 99%
“…Among the 121 BC patients, candidates for exclusive hormone therapy without the Oncotype Dx, 18 (15%) patients obtained an RS that referred to chemotherapy treatment followed by hormone therapy. The percentage of patients initially recommended for hormone therapy alone for whom the recommendation changed to chemotherapy plus hormone therapy was low (7%) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%